Thyroid Hormones Regulate Zebrafish Melanogenesis in a Gender-Specific Manner. - Raúl Guillot; Borja Muriach; Ana Rocha; Josep Rotllant; Robert N Kelsh; José Miguel Cerdá-Reverter (PLoS ONE)
Zebrafish embryos are treated with anti-thyroidal compounds, such as phenylthiourea, to inhibit melanogenesis. However, the mechanism whereby the thyroidal system controls melanin synthesis has not been assessed in detail. In this work, we tested the effect of the administration of diets supplemented with T3 (500μg/g food) on the pigment pattern of adult zebrafish. Oral T3 induced a pronounced skin paling in both adult female and male zebrafish that was reversible upon cessation of treatment. The number of visible melanophores was significantly reduced in treated fish. Accordingly, treatment down-regulated expression of tyrosinase-related protein 1 in both sexes. We also found sexually dimorphic regulation of some melanogenic genes, such as Dct/Tyrp2 that was dramatically up-regulated in females after T3 treatment. Thus, we demonstrated that melanogenesis is reversibly inhibited by thyroid hormones in adult zebrafish and make the discovery of gender-specific differences in the response of melanogenic gene expression. Thus, fish gender is now shown to be an important variable that should be controlled in future studies of fish melanogenesis.